Determinación del comportamiento productivo del vástago de banano fermentado (Musa paradisiaca) en la alimentación de cerdo, en la fase de crecimiento - Vivas Castillo, Paola Jamileth (2024)
The objective of this research work was to determine the productive behavior of the fermented banana stem (Musa paradisiaca) in pig feeding, in the growth phase. The duration was 45 days. Nine pigs, corn flour, protein concentrate and banana stem fermented for eight days were used. A completely randomized design (DCA) was used, with three treatments and three repetitions. Each experimental unit was composed of three pigs. The data were analyzed with the Infostat statistical software, with a significance level P ≤ 0.05. T0 was included in the diet: 60% Corn Flour + 39% commercial concentrate + 1% mineral salt; T1 included 45.48% corn flour + 39.42% commercial concentrate + 15% fermented banana stem; and for T2, 39.77% of Corn Flour + 40.23% of commercial Concentrate + 20% of the fermented banana stem were included. T1 was the one with the highest consumption in weeks 1,2,4,5 and 6; (3.10 kg, 4.11 kg, 7.17 kg, 8.16 kg and 10.19 kg). The T1 weight was higher in all six weeks (9.74 kg; 12.19 kg; 15.42 kg; 19.79 kg; 24.21 kg; 27.96 kg). The one that achieved the greatest weight gain in T1 in week 1 and 3 (1.89 kg; 3.23 kg), the T2 treatment achieved in week 2 and 5 (2.50 kg; 5.22 kg). The best feed conversion was achieved by T1 in weeks 1, 3 and 4 (1.73 g/g; 2.38 g/g; 1.70 g/g).